Volumetric and ultrasonic investigation of polyethylene glycols (PEG-200 and PEG-600) in aqueous solutions of sodium methylparaben at various temperatures. (January 2020) - Ashima,; Juglan, K.C.; Kumar, Harsh
Highlights: Physicochemical properties of PEGs were studied in aqueous SMP solutions. Apparent molar properties of PEGs and SMP in aqueous medium signify the dominance of solute-solvent interactions. Structure building tendency of PEGs in aqueous SMP solutions is estimated from the data. Pairwise interactions among PEGs and SMP in aqueous medium are predicted by pair and triplet coefficients. Abstract: In the current work, the apparent molar properties and partial molar properties have been assessed from the measurement of density and speed of sound with the interest to inspect the interconnection of polyethylene glycols viz . PEG-200 and PEG-600 in aqueous solutions of sodium methylparaben at several temperature varying from 293.15 K to 308.15 K and experimental pressure p  = 0.1 MPa. The investigation of apparent molar volume ( V ϕ ), partial molar volume ( V ϕ 0 ) and partial molar volume of transfer ( Δ V ϕ 0 ) is performed using density measurements. The data of apparent molar isentropic compression ( K ϕ, s ), partial molar isentropic compression ( K ϕ, s 0 ) together with partial molar isentropic compression of transfer ( Δ K ϕ, s 0 ) are attained with the aid of speed of sound measurements. The limiting apparent molar expansibilities ( E ϕ 0 ) along with its first order derivative ( ∂ E ϕ 0 / ∂ T ) P are also evaluated. Moreover, utilizing McMillan and Mayer theory of liquids, the pair and triplet coefficients are estimated from the experimental data. Through the examination of these computed parameters, the results are illuminated with reference to physicochemical co-solute-solvent association arising in the existing investigated system.